Intraclass diversification of immunoglobulin heavy chain genes in the African lungfish - Zhang, Tianyi (Immunogenetics, 2014)
Lungfish (Dipnoi) are the closest living relatives to tetrapods, and they represent the transition from water to land during vertebrate evolution. Lungfish are armed with immunoglobulins (Igs), one of the hallmarks of the adaptive immune system of jawed vertebrates, but only three Ig forms have been characterized in Dipnoi to date. We report here a new diversity of Ig molecules in two African lungfish species (Protopterus dolloi and Protopterus annectens). The African lungfish Igs consist of three IgMs, two IgWs, three IgNs, and an IgQ, where both IgN and IgQ originated evidently from the IgW lineage. Our data also suggest that the IgH genes in the lungfish are organized in a transiting form from clusters (IgH loci in cartilaginous fish) to a translocon configuration (IgH locus in tetrapods). We propose that the intraclass diversification of the two primordial gnathostome Ig classes (IgM and IgW) as well as acquisition of new isotypes (IgN and IgQ) has allowed lungfish to acquire a complex and functionally diverse Ig repertoire to fight a variety of microorganisms. Furthermore, our results support the idea that “tetrapod-specific” Ig classes did not evolve until the vertebrate adaptation to land was completed ∼360 million years ago.